2002
DOI: 10.2170/jjphysiol.52.135
|View full text |Cite
|
Sign up to set email alerts
|

Strenuous Exercise-Induced Change in Redox State of Human Serum Albumin during Intensive Kendo Training.

Abstract: Serum albumin is the most abundant protein in extracellular fluids such as blood plasma and interstitial fluid. One of the most important features of the molecular structure of albumin is the presence of a highly reactive free sulfhydryl group in position 34

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
3
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 26 publications
(40 reference statements)
5
56
3
5
Order By: Relevance
“…2-5). This suggests that PCB126 administration had an influence on the change in the form of Alb, i.e., hepatic toxicity accompanying the increase in mercaptoalbumin 9) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2-5). This suggests that PCB126 administration had an influence on the change in the form of Alb, i.e., hepatic toxicity accompanying the increase in mercaptoalbumin 9) .…”
Section: Resultsmentioning
confidence: 99%
“…Middle: Administered rats in the PCB 126 group (5)(6)(7)(8). Bottom: Administered rats in the PCB 169 group (9)(10)(11)(12). The spots shown by solid line arrows in the rats of the PCB groups were markedly increased, as compared to those in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…The fraction of oxidized albumin is also increased in diabetes mellitus (53), disorders of the temporomandibular joint (54), senile cataract (55), and invasive surgery (56). Furthermore, it has been shown that the fraction of oxidized albumin also increases with aging (26,35) and intense exercise (57).…”
Section: Implications In Pathologymentioning
confidence: 99%
“…Υπάρχουν μελέτες, οι οποίες έχουν δείξει την επίδραση της έντονης άσκησης στο οξειδοαναγωγικό σύστημα της ανθρώπινης αλβουμίνης του ορού (Imai et al, 2002;Lamprecht et al, 2008Lamprecht et al, , 2009). Πιο συγκεκριμένα, βρέθηκε ότι η έντονη άσκηση αυξάνει την οξειδωμένη αλβουμίνη (Imai et al, 2002) και οι οξειδωτικές τροποποιήσεις εξαρτώνται από την ένταση της άσκησης (Lamprecht et al, 2008(Lamprecht et al, , 2009. Επιπλέον, η οξειδωμένη αλβουμίνη έχει προταθεί ως δείκτης οξειδωτικού στρες (Lamprecht et al, 2009).…”
Section: ο αντιοξειδωτικός ρόλος της αλβουμίνηςunclassified
“…Πιο συγκεκριμένα, βρέθηκε ότι η άσκηση αύξησε την οξειδωμένη αλβουμίνη του ορού (Imai et al, 2002) και μάλιστα ότι η οξειδωτική τροποποίηση του μορίου της είναι εξαρτώμενη από την ένταση της άσκησης (Lamprecht et al, 2008(Lamprecht et al, , 2009. Τα αποτελέσματα αυτά είναι σε συμφωνία με την αύξηση της συγκέντρωσης της αλβουμίνης που παρατηρήσαμε στους σκελετικούς μύες.…”
Section: 4unclassified